Architecture design and development for real-time risk-based unmanned aerial system traffic management - Ra, Thu (2021)
Deploying Unmanned Aircraft System in industrial missions has been a heating topic in recent years. Because of the rapid development of UAS flight control, artificial intelligence, as well as communication, navigation, and surveillance (CNS) systems, UAS has been showing a promising performance that satisfy the requirement of being utilized in transportations. However, current air traffic management system is not suitable to provide services to UAS traffic that is significantly different from conventional air traffic in terms of aircraft characteristics, operational environment, and mission types. In this paper, a UAS traffic management (UTM) system is developed. The system enables both strategical and tactical flight planning capabilities and provides interfaces for both UAS service providers and operators.